Adapting Street Profile Design by Using Nature-Based Solutions in New Neighbourhoods and the Retrofit of Buildings - Adrian Ibric; Maria Bostenaru Dan; Cerasella Crăciun (Buildings, 2024)
The aim of this paper is to analyse ways to upgrade the existing urban and architectural features in the built environment by incorporating and enhancing the use of nature-based solutions (NbSs) in relation to the city of Bucharest, which lacks green spaces mapping and quality studies and literature. The paper draws a comparison between the design elements used in other cities, namely Lisbon, Vienna and Rome. These are also analysed and compared in relation to the integration in a mixed urban development plan for a research-to-business neighbourhood design competition in Măgurele, situated near Bucharest. A matrix of five criteria is used for the analysis: historical context, urban context, nature versus design, use and climate context. In Lisbon, examples range from new green walls, modern green Mediterranean courtyards, NbS in scaffolding and temporary walls, the placing of Miradores around the city to green-and-healthy marketing tools for restaurants. For Vienna, a street is being remodelled in an innovative way using independent green infrastructure designs in existing retrofitted parking units, hotels and residential constructions. For Bucharest, emergent pop-up, small scale, bottom-up solutions push the city’s urban fabric beyond the greyish look of socialist-communist background and eclectic late 19th, early 20th century built heritage. For Măgurele, different versions of a modern neighbourhood and street profile design issues are analysed, using 3D renderings that incorporate NbS at various insertion scales. Existing example cases showcase new dimensions and toolsets of the adaptation of the urban fabric based on a more ecosystem-based approach of architectural-urban research by design, as possible instruments that facilitate a Green Transition in urban settings. Covering more cities in the future would add to the impact and contribution of this study.